MINAT SISWA KELAS V MADRASAH IBTIDAIYAH MUHAMMADIYAH SUKAJATI HAURGEULIS TERHADAP PELAJARAN BAHASA INDONESIA - Giarto Giarto; Moch. Hasyim Fanirin (Bajang Institute, 2022)
The phenomenon that occurs in the school environment and in the community is that there are still many school-age children who use regional languages as the language of daily communication, from this phenomenon the author wants to examine the learning interest of class V students towards learning interest in Indonesian at Madrasah Ibtidaiyah Muhammadiyah Sukajati Haurgeulis problems in research This is how the interest of grade v students towards Indonesian language lessons, what factors influence the interest of grade V students towards Indonesian language lessons. This research method uses descriptive qualitative by using a qualitative naturalistic approach. The object of this research is the fifthgrade students of Madrasah Ibtidaiyah Muhammadiyah at Madrasah Ibtidaiyah Sukajati Haurgeulis 2018/2019, totaling 22 students and Indonesian Language Teachers. The data sources of this study use primary data and secondary data. Research procedures or data collection techniques using observation, interviews, documentation and questionnaires The results of research at Madrasah Ibtidaiyah Muhammadiyah Sukajati Haurgeulis can be concluded that the learning interest of grade V students towards Indonesian language lessons still needs to be improved or not optimal. The lack of optimal is due to the lack of variation in learning methods and motivation from parents so that students are less interested in Indonesian language lessons